If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 12 = -43 + -7x Reorder the terms: 12 + 4x = -43 + -7x Solving 12 + 4x = -43 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 12 + 4x + 7x = -43 + -7x + 7x Combine like terms: 4x + 7x = 11x 12 + 11x = -43 + -7x + 7x Combine like terms: -7x + 7x = 0 12 + 11x = -43 + 0 12 + 11x = -43 Add '-12' to each side of the equation. 12 + -12 + 11x = -43 + -12 Combine like terms: 12 + -12 = 0 0 + 11x = -43 + -12 11x = -43 + -12 Combine like terms: -43 + -12 = -55 11x = -55 Divide each side by '11'. x = -5 Simplifying x = -5
| 109-5x=3x+21 | | -40-3x=9-10x | | 5x+13=93-5x | | 10+6x=30+x | | 5x-4=12x-60 | | 2x+36=11x-36 | | 2x+51=6x+11 | | 2x+21=6x+11 | | 2y+5=-9 | | 2y= | | 3x+5=166 | | 57+83= | | 5x+14=5x+24 | | -8p=88 | | (5v+2)(1+v)=0 | | 3d=57 | | -3y-8=11 | | 5x-2y=19 | | 0.35+0.24x=0.2(5-3x) | | 12x-11x-24=8 | | 5x-4x-10=13 | | 17y-2=88-y | | -3x-148+11x=84 | | -3x-9x^2= | | 1.5+3.8= | | 0.5x+0.2(3-2x)=0.04 | | 0.2x-0.3(5-2x)=0.4 | | 119-6x=12x+23 | | 8-9x=93-44x | | -87-9x=8x+15 | | 12x+9-5=11x-3 | | 5x+9=-63-7x |